Electronic Judiciary (E-Court) from the Perspective of Maslahah Theory and Its Correlation with the Realization of a Supreme Judicial Institution - Azis, Fitriah; Nugraha , Alfajar; Firdaos, Mochamad (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2025)
The advancement of information technology has significantly driven reform within Indonesia’s judicial system, particularly through the implementation of an electronic court system (e-Court). This article aims to analyze e-Court from the perspective of maslahah theory in Islamic law and to assess its contribution to the realization of a supreme and dignified judiciary. Employing a qualitative-descriptive approach through a literature review method, this study evaluates the relevance of maqāṣid al-sharī‘ah values in the e-Court system. The findings reveal that e-Court not only enhances administrative efficiency but also aligns with the core principles of Islamic law, such as the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), wealth (ḥifẓ al-māl), and religion (ḥifẓ al-dīn). During the pandemic, the role of e-Court evolved from serving a secondary need to becoming a primary necessity due to its function in safeguarding human existence. Therefore, the e-Court system can be regarded as a strategic instrument for supporting a judicial institution that is inclusive, adaptive, and oriented toward public benefit (maslahah). This study recommends strengthening the implementation of e-Court based on Islamic values to ensure comprehensive substantive justice for society. [Perkembangan teknologi informasi telah mendorong reformasi signifikan dalam sistem peradilan Indonesia, salah satunya melalui implementasi sistem peradilan elektronik (e-Court). Artikel ini bertujuan untuk menganalisis e-Court dari perspektif teori maslahah dalam hukum Islam dan menilai kontribusinya terhadap perwujudan lembaga peradilan yang agung. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan metode studi pustaka untuk mengevaluasi relevansi nilai-nilai maqāṣid al-sharī‘ah dalam sistem e-Court. Hasil kajian menunjukkan bahwa e-Court tidak hanya efisien secara administratif, tetapi juga sejalan dengan prinsip-prinsip syariat, seperti perlindungan terhadap jiwa (hifẓ al-nafs), akal (hifẓ al-‘aql), harta (hifẓ al-māl), dan agama (hifẓ al-dīn). Dalam situasi pandemi, e-Court bahkan telah meningkat kedudukannya dari kebutuhan sekunder menjadi kebutuhan primer karena perannya dalam melindungi eksistensi manusia. Oleh karena itu, sistem e-Court dapat diposisikan sebagai instrumen strategis dalam mendukung lembaga peradilan yang inklusif, adaptif, dan maslahat. Penelitian ini merekomendasikan penguatan implementasi e-Court berbasis nilai-nilai keislaman guna memastikan keadilan substantif yang menyeluruh bagi masyarakat.]